2002
DOI: 10.1038/sj/jim/7000244
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular detection of crystalliferous Bacillus thuringiensis strains from habitats in the South Central United States

Abstract: Gram-positive, endospore-forming Bacillus thuringiensis-like strains were isolated from 95 of 413 samples collected at the 0-5 cm depth of noncultivated soils and stagnant or dried-up ponds as well as from dust from stored grain products in South Central United States. Based on the production of parasporal crystals, 25 isolates were identified as B. thuringiensis after examining 227 B. thuringiensis-like colonies. The greatest proportion of samples yielding B. thuringiensis were from the dust from grain storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Bacillus thuringiensis bacteria are ubiquitous in soil [2, 13, 33, 34], dead larvae [4], sand [5], leaves [3], water [7], or dust from stored grains [6]. Wild strains isolated form environmental samples can synthesize crystals that display higher activity against insect pests in comparison to B. thuringiensis strains already used in pesticide production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacillus thuringiensis bacteria are ubiquitous in soil [2, 13, 33, 34], dead larvae [4], sand [5], leaves [3], water [7], or dust from stored grains [6]. Wild strains isolated form environmental samples can synthesize crystals that display higher activity against insect pests in comparison to B. thuringiensis strains already used in pesticide production.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were also noted as the most frequent in B. thuringiensis strains [2, 3, 5, 6, 33, 34]. All analyzed B. thuringiensis harbored cry1I genes that have been reported as the most abundant in B. thuringiensis isolates [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 202 colonies analyzed by PCR, 10 were positive for any of the five genes analyzed by multiplex PCR (cry2, cry4, cry10, cry11, cry19), endpoint PCR for each of the 10 positive samples with primers reported in the literature was used (Carozzi et al 1991, Ejiofor andJohnson 2002), only seven colonies that showed a single band corresponding to the expected size were selected for further analysis, and these were characterized by light microscopy based on the shape of the crystal ( Table 1). The protein crystals were characterized by SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Five pairs of primers (2M, 4M, 10M, 11M, and 19M) were designed for multiplex PCR with the software Mpprimer (Shen et al 2010); primer pair 2M: 5'-ACCCCAGTTCCAGATGCAAGGA/ 5'-TGCTGTGGTCCACTACCACTTGC, product size 369 bp for the gene cry2; 4M: 5'-TGGATGCACGAGTGGCACAAGC/ 5'-GCATTTCCAGTTACATGCCACCCCA, product size 106 bp for the gene cry4; 10M: 5'-CGCAACATAATCTGGGGAGCGGT/ 5'-TCCACCTGTGTGACCAGGACCTT, product size 468 bp for the gene cry10; 11M: 5'-TTTAACTGCGCCAGCACCAGCA/ 5'-ACCCGTATTCCAGCAGGTAAGCGA, product size 588 bp for the gene cry11; 19M: 5'-CGAGGAAGCTTCTTATGCATCTTCAGG/ 5'-CACGCAGCGAGAGCTCGGTTAT, product size 291 bp for the gene cry19, with the corresponding Tm of 59.2°C for all the previous primer pairs, these primers were used for partial classification of genes by multiplex PCR. Subsequent PCR primers reported in the literature (Carozzi et al 1991, Ejiofor andJohnson 2002) were used to confirm the presence of the cry genes by uniplex PCR: primer pair 4U: 5'-CAAGCCGCAAATCTTGTGGA/ 5'-TGGCTTGTTTCGCTACATC, product size 797 bp, for the gene cry4 (Carozzi et al 1991); 10U: 5'-TCGTGGAATGGGCAAAAAC/ 5'-TATCCCCCTTCAACATCCTCA, product size 404 bp for the gene cry10; 11U: 5'-TTTGCACCAGATAATACTAAGGAC/ 5'-AACAACTGCGATAAATACCACTCT, product size 485 bp for the gene cry11; 19U: 5'-AGGGGAGTCCAGGTTATGAGTTAC/ 5'-ATTTCCCTAGTTAGTTCGGTTTTT, product size 355 bp for the gene cry19 (Ejiofor and Johnson 2002), with the corresponding Tm of 55°C for all the previous primer pairs.…”
Section: Methodsmentioning
confidence: 99%